Formulation and Evaluation of Chlorhexidine Medicated Chewing Gums by Different Methods - Rajitha, Koppula (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The aim of this work is development and evaluation of chlorhexidine medicated chewing gums by different methods and to study the influence of different plasticizers and methods on physicochemical parameters and in vitro drug release profile. Materials and Methods: Chlorhexidine is an antibacterial agent used for management of tooth decay. The formulations are prepared with varying concentrations of plasticizers and synthetic gum base by different methods such as direct compression and melting method. The prepared formulations are evaluated for thickness, hardness, weight variation, friability, stickiness, color, drug content, and drug-excipient interations. In vitro drug release was performed by modified dissolution apparatus. Results and Discussion: The formulations prepared by direct compression method with castor oil as a plasticizer, i.e., F11 shows good drug release compared to formulations prepared with glycerin. In melting method, as the gum base concentration increases, the in vitro drug release is increased. The formulations prepared with both methods show good drug release, but direct compression formulations show high drug release compared to formulations prepared by melting process. Conclusion: This study indicates that it is the better choice to prepare medicated chewing gums of chlorhexidine by different methods to improve the patient acceptance.